Engineering a three-dimensional, photoelectrochemically active p-NiO / i-Sb2S3 junction by atomic layer deposition. (10th October 2015) - Barr, Maïssa K.S.; Assaud, Loïc; Wu, Yanlin; Laffon, Carine; Parent, Philippe; Bachmann, Julien; Santinacci, Lionel
Abstract: A p-NiO / i-Sb2 S3 semiconductor junction is created as an array of parallel, coaxially structured, hollow nanocylinders. The preparation bases on two consecutive steps of atomic layer deposition (ALD) onto the pore walls of anodic alumina, used as an inert template. ALD allows for the conformal coating of the deep pores. Characterization by x-ray photoelectron spectroscopy, x-ray diffraction, and transmission electron microscopy demonstrates the high purity, perfect stoichiometry, and nanocrystalline structure of both layers. Annealing the samples increases the crystallite size but disrupts the continuity of the Sb2 S3 film. Electrochemical and photoelectrochemical curves evidence the injection of holes from the light absorber Sb2 S3 into the p-type NiO, but no significant photoinduced cathodic electron transfer to the electrolyte.